Pengaruh Pertumbuhan Penjualan, Ukuran Perusahaan, Struktur Aset dan Profitabilitas terhadap Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2015 - Nelli Novyarni; Lisna Wati (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2018)
Capital structure is the ratio or the balance between foreign capital and equity capital that affect decision making employment decisions. Where the capital structure is influenced by sales growth, company size, structure and profitability of assets. This study aims to influence sales growth, company size, structure and profitability of assets partially and simultaneously the capital structure on companies listed on the Stock Exchange. The research strategy used in this study is a research strategy associative. The method of research used in this research is quantitative method. In this study population was used as the financial statements of companies listed on the Stock Exchange. Samples taken by the researchers was 35 manufacturing companies that go public in BEI using data from the financial statements of the balance sheet and income statement in the period 2012-2015. The analytical tool used is Eviews 9.0. Based on the analysis and discussion show sales growth and no significant effect on the capital structure on companies listed on the Stock Exchange. The size of the company and significant effect on the capital structure of companies listed on the Stock Exchange. The structure of assets and significant effect on the capital structur e of companies listed on the Stock Exchange. Profitability and no significant effect on the capital structure on companies listed on the Stock Exchange. Based on the results of simultaneous hypothesis testing the rate of sales growth, company size, structure and profitability of assets simultaneously significantly affect the capital structure means the hypothesis is proved significant.